2014
DOI: 10.1124/jpet.114.215145
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Baicalin on Collagen-Induced Arthritis in Rats through the Nuclear Factor–κB Pathway

Abstract: This study focused on the potential therapeutic effect of baicalin on collagen-induced arthritis (CIA) in rats and the underlying mechanisms. The CIA rats were injected with baicalin (50, 100, or 200 mg/kg) once daily for 30 days. The rats were monitored for clinical severity of arthritis, and joint tissues were used for radiographic assessment and histologic examination. We quantified tumor necrosis factor-a (TNF-a) and interleukin-1b (IL-1b) in experimental animals and used Western blots to assess levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…These results suggest that baicalin may attenuate upper airway remodeling. These results are consistent with those of previous studies that reported that baicalin inhibited IL-1β secretion and has therapeutic effects on collagen-induced inflammation in human fibroblast-like synoviocytes and a rat model of collagen-induced arthritis [25]. …”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that baicalin may attenuate upper airway remodeling. These results are consistent with those of previous studies that reported that baicalin inhibited IL-1β secretion and has therapeutic effects on collagen-induced inflammation in human fibroblast-like synoviocytes and a rat model of collagen-induced arthritis [25]. …”
Section: Discussionsupporting
confidence: 93%
“…Dinda et al reported that baicalin inhibited reactive oxygen species (ROS) production in arteriosclerotic vascular disease by suppressing the activation of the NF-κB signaling pathway (17). Wang et al reported that baicalin exerts an inhibitory effect on inflammation-related collagen-induced arthritis via inhibition of the activation of the NF-κB signaling pathway (18). Given its ability to inhibit the activation of NF-κB signaling, it was hypothesized that baicalin may suppress breast cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, previous studies have shown that baicalin has antidepressant‐like effects and decreases serum corticosterone levels in various depression models (Li et al, ; Yu et al, ; Zhang et al, ; Yu et al, ; Zhang et al, ). Although several recent studies have been conducted to investigate the antidepressant effect of baicalin, few studies have evaluated the mechanism of baicalin reverses inflammation on collagen‐induced arthritis in rats, which is related to the elevation of NF‐κB p65 protein deacetylation by SIRT1 (Wang et al, ). Thus, we hypothesized that baicalin reverses the depression‐like behavior and inflammation in depression via regulation of the SIRT1‐NF‐κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%